2019
DOI: 10.1088/1741-4326/ab0975
|View full text |Cite
|
Sign up to set email alerts
|

Tamed stability and transport using controlled non-axisymmetric fields in KSTAR

Abstract: Meticulously orchestrated non-axisymmetric fields (δB) enabled KSTAR to explore various paths to tame plasma stability and transport in a very rigorous manner. Given an extremely low level of intrinsic non-axisymmetry, KSTAR has now established high-precision 3D field control capability that can not only robustly suppress edge localized modes (ELM) using resonant magnetic perturbation (RMP), but also exclusively alter plasma rotation without invoking particle and energy transport. In highly shaped plasmas (tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 32 publications
6
38
0
Order By: Relevance
“…However, once the near-scrapeoff-layer (SOL) peaks are normalized, the divertor heat fluxes under 3-row IMCs have been broadened but nothing similar appears in 2-row RMPs, as shown in Figure 6 (b) and (d). This reminds us of a similarly contrasting observation of divertor heat fluxes between ELM-crash-suppression and ELM-crash-mitigation [5], in which the divertor heat flux dispersal was observed only during ELM-crash-suppression, while nothing similar appears during ELM-crash-mitigation. So far, when the IMC with "away" phasing is reinforced by the global 'kink-resonant' influences, such broadening has been speculated to be readily available in a non-linear plasma simulation [5].…”
Section: Divertor Heat Flux Dispersal In 3-row Imc and 2-row Rmpssupporting
confidence: 52%
See 1 more Smart Citation
“…However, once the near-scrapeoff-layer (SOL) peaks are normalized, the divertor heat fluxes under 3-row IMCs have been broadened but nothing similar appears in 2-row RMPs, as shown in Figure 6 (b) and (d). This reminds us of a similarly contrasting observation of divertor heat fluxes between ELM-crash-suppression and ELM-crash-mitigation [5], in which the divertor heat flux dispersal was observed only during ELM-crash-suppression, while nothing similar appears during ELM-crash-mitigation. So far, when the IMC with "away" phasing is reinforced by the global 'kink-resonant' influences, such broadening has been speculated to be readily available in a non-linear plasma simulation [5].…”
Section: Divertor Heat Flux Dispersal In 3-row Imc and 2-row Rmpssupporting
confidence: 52%
“…Although the choice of 3-row ITER RMP is greatly meritorious in this aspect, the physics question about the broadening mechanism needs to be further clarified. While the IMC with "away" phasing greatly benefited from a global 'kink-resonance' that would interact with edge RMP coupling [5], it remains to be answered what causes the IMC with "toward" phasing to be similarly accompanied by divertor heat flux broadening. Based on Fig.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…1 The application of resonant magnetic perturbation (RMP) is proposed to relieve the heat flux onto the PFC by controlling the ELM-crash. Since the first demonstration of ELM-crash suppression by the RMP technique in DIII-D experiment, 2 various tokamaks have confirmed that the RMP would be an ideal tool to control the ELM-crashes effectively in either suppression or mitigation: KSTAR, [3][4][5][6][7] ASDEX Upgrade, 8,9 MAST, 10 and JET. 11 The access conditions to ELM-crash suppression have been investigated to establish robust and reliable ELM-crash control.…”
Section: Introductionmentioning
confidence: 99%
“…18 KSTAR has provided results to understand the physics and effects of RMP-driven ELM-crash suppression based on the high reproducibility of the suppression. [4][5][6][7]19,20 In KSTAR, the RMP-driven ELM-crash suppression phase is highly sustainable, in that the longest suppression phase was stably sustained up to the time scale of wall saturation by deuterium fuel ($30 s). 6 Therefore, KSTAR provides one of the best testbeds to address the remaining uncertainties of ELM-crash control in ITER.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation